Southwestern Nigerian University Undergraduates’ Acceptance of YouTube as a web-based Instructional Tool - Oteyola, Temitope; Bada, Tayo; Akande, Itunu (Advances in Social Sciences Research Journal, 2019)
The study assessed the Southwestern Nigerian undergraduates’ acceptance of YouTube as a web-based instructional tool using Unified Theory of Acceptance and Use of Technology (UTAUT) Model. It determined the level of awareness of YouTube as a web-based instructional tool by the undergraduates. It measured the undergraduates’ effort and performance expectancy of YouTube and the conditions that facilitate its acceptance at the universities. The study employed the descriptive survey research design. The population consisted all registered undergraduates in Southwestern Nigeria. 800 students were selected from Obafemi Awolowo University (OAU), Ile-Ife, Osun State, Ladoke Akintola University of Technology (LAUTECH), Oyo State and Covenant University, Ota, Ogun State using disproportionate stratified sampling. The three universities were purposively selected based on their webometric ranking in terms of ICT usage. Findings from the study indicated that 57.80% of the undergraduates are moderately aware of YouTube as an instructional tool. The effort expectancy (×̅=3.00, sd=0.60) as well as the performance expectancy (×̅=3.00, sd=0.62) show that the undergraduates accept YouTube. The conditions identified by the undergraduates that can militate the acceptance of YouTube in the region included low bandwidth (79.70%), low hard disk space (65.60%), epileptic electricity supply (68.60%) and high cost of required devices (68.40%). The study therefore concluded that Southwestern Nigerian undergraduates are prone to accepting YouTube as a web-based instructional tool. The study assessed the Southwestern Nigerian undergraduates’ acceptance of YouTube as a web-based instructional tool using Unified Theory of Acceptance and Use of Technology (UTAUT) Model. It determined the level of awareness of YouTube as a web-based instructional tool by the undergraduates. It measured the undergraduates’ effort and performance expectancy of YouTube and the conditions that facilitate its acceptance at the universities. The study employed the descriptive survey research design. The population consisted all registered undergraduates in Southwestern Nigeria. 800 students were selected from Obafemi Awolowo University (OAU), Ile-Ife, Osun State, Ladoke Akintola University of Technology (LAUTECH), Oyo State and Covenant University, Ota, Ogun State using disproportionate stratified sampling. The three universities were purposively selected based on their webometric ranking in terms of ICT usage. Findings from the study indicated that 57.80% of the undergraduates are moderately aware of YouTube as an instructional tool. The effort expectancy (×̅=3.00, sd=0.60) as well as the performance expectancy (×̅=3.00, sd=0.62) show that the undergraduates accept YouTube. The conditions identified by the undergraduates that can militate the acceptance of YouTube in the region included low bandwidth (79.70%), low hard disk space (65.60%), epileptic electricity supply (68.60%) and high cost of required devices (68.40%). The study therefore concluded that Southwestern Nigerian undergraduates are prone to accepting YouTube as a web-based instructional tool.